The effect of problem-based learning on cognitive skills in solving geometric construction problems: a case study in Kazakhstan - Tursynkulova, Elmira; Madiyarov, Nurlybay; Sultanbek, Turlybek; Duysebayeva, Peruza (Frontiers in Education, 2023)
This study aims to investigate the impact of a Problem-Based Learning (PBL) course on cognitive skills (i.e., Critical Thinking, Problem-Solving, Logical Reasoning, Creativity, and Decision-Making) in the context of solving geometric construction problems. The research utilized a quasi-experimental design involving a control group and an experimental group to assess the effects of the PBL intervention. Cognitive skills were measured using a custom-designed questionnaire. Additionally, Structural Equation Modeling (SEM) was employed in a subsequent phase to scrutinize the causal interrelationships among these cognitive skills. In the initial phase, the findings revealed that the PBL intervention had a statistically significant positive impact on problem-solving and creativity skills. However, the effects on critical thinking, logical reasoning, and decision-making skills did not reach statistical significance. In the subsequent phase employing SEM, the analysis demonstrated significant positive relationships, particularly between critical thinking and problem-solving, critical thinking and logical reasoning, logical reasoning and problem-solving, and logical reasoning and creativity. Notably, creativity also exhibited a significant positive effect on problem-solving. This study underscores the nuanced impact of PBL on different cognitive skills, with clear enhancements observed in problem-solving and creativity. However, the study suggests that the effects may not be uniform across all cognitive skills. These findings offer valuable insights for educators and curriculum designers, emphasizing the need for tailored approaches when integrating PBL to foster cognitive skill development.